Force Majeure Management of Islamic Boarding Schools During the Covid-19 Pandemic (Force Majeure Pengelolaan Pesantren di Masa Pandemi Covid-19) - Badarwan, Badarwan; Sumardona, Sumardona (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
This article aims to systematically describe force majeure in Islamic boarding school management, especially during the Covid-19 pandemic. The aspects studied are Islamic boarding school policies in responding to the Covid-19 pandemic phenomenon and the technological readiness of Islamic boarding schools. This research is qualitative research with a narrative approach, where various information is presented systematically as a series of events that have meaning. The research results show that: First, the Annur Azzubaidi Islamic boarding school issued a social restriction policy, not sending students home, so that educational activities were still ongoing. Second, technological readiness is very low, due to the boarding school's perspective which places more emphasis on providing traditional education. Accommodation and adaptation of technology is done slowly and very carefully. Socialization of Islamic boarding schools, especially during the season for accepting new students, is still carried out using traditional methods, without utilizing the latest technological products, for example the use of social media (in its various variants). This condition is an emanation of the attitude and consistency of the boarding school leaders towards the basic values that they believe in. The Annur Azzubaidi Islamic boarding school was founded to seek blessings from God, build the Qur'an generation, so as far as possible to prevent worldly competition.Keywords: Force Majeure, Islamic Boarding School Traditions, Covid-19